Permeability measurements of Ni0.4Cu0.15Zn0.45Fe2O4 using impedance analyzer - Shara, Afrin Jahan (BRAC Univeristy, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.